MicroRNA-19a and CD22 Comprise a Feedback Loop for B Cell Response in Sepsis - Jiang, Yinan (Med Sci Monit, 2015)
BACKGROUND: MicroRNA-19a (miR-19a), an oncogenic microRNA, has been recently reported to target CD22 in B cell lymphoma cell lines, but its role in inflammatory response is unclear. CD22 is a negative regulator for BCR signaling, and we hypothesize that miR-19a regulates B cell response by targeting CD22 in sepsis. MATERIAL/METHODS: In order to determine whether miR-19a-CD22 pathway was involved in sepsis, and what role it played in the regulatory mechanisms, we detected the levels of miR-19a in B cells obtained from patients with sepsis, and measured the levels of miR-19a and CD22 expression in B cells activated by LPS in vitro. Additionally, we investigated the correlation between miR-19a and CD22, as well as the influence of this pathway on BCR signaling, in transfected B cells. RESULTS: We found that septic patients displayed up-regulated miR-19a in B cells. In vitro, miR-19a was increased in activated B cells, with CD22 expression initially enhanced but subsequently decreased. Moreover, overexpression of miR-19a resulted in an amplified BCR signaling, while overexpression of CD22 attenuated the effect of miR-19a and increased its expression. CONCLUSIONS: Our study demonstrated that miR-19a and CD22 comprised a feedback loop for B cell response in sepsis, providing a potential therapeutic target to recover the immune homeostasis.